2018
DOI: 10.1002/mame.201700378
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Mussel‐Inspired Multifunctional Polymeric Membranes with Remarkable Anticoagulant, Antifouling, and Antibacterial Properties

Abstract: Herein, a facile one‐step surface modification technique of coating functional biopolymer conjugated mussel‐inspired catechol (CA) onto substrate is applied to confer polyethersulfone (PES) membranes with remarkable blood compatibility, antifouling property, and antibacterial property, respectively. CA conjugated poly(2‐acrylamido‐2‐methylpropanesulfonic acid) (PAMPS), poly(sulfobetaine methacrylate) (PSBMA), and poly(methacryloxyethyltrimethyl ammonium chloride) are synthesized via free radical polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Many researchers found that membrane surface modification using polymers with adsorption function could improve the removal abilities of membranes for micropollutants . Inspired by the strong adhesion of mussel proteins, dopamine coating technology provided a versatile platform for construction of varied functional membranes . The combination of adsorption and separation process could impart a wider application prospect to these modified membranes …”
Section: Introductionmentioning
confidence: 99%
“…Many researchers found that membrane surface modification using polymers with adsorption function could improve the removal abilities of membranes for micropollutants . Inspired by the strong adhesion of mussel proteins, dopamine coating technology provided a versatile platform for construction of varied functional membranes . The combination of adsorption and separation process could impart a wider application prospect to these modified membranes …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Nevertheless, PSf material is hydrophobic by nature; when it is used as blood-contacting membranes, a series of bioresponses such as apparent protein adsorption, platelet adhesion, and the activation of the clotting enzyme will occur, which directly leads to thrombogenesis. 8,9 Therefore, it is reasonable and necessary to modify pristine PSf to ameliorate its hemocompatibility.…”
Section: Introductionmentioning
confidence: 99%